Atomic Layer Deposition Reinforcement of Methylcellulose Nanowire Forests. Issue 7 (30th January 2022) - Nachtigal, Catherine J.; Li, Yi; Zhang, Li; Lei, Lin; Losego, Mark D.; Singer, Jonathan P.
Abstract : Micro‐ and nanostructured surfaces are widely used as functional surfaces in various fields including the maritime and medical industries. Many micro‐ and nanocoating technologies are delicate processes that have high costs at scale. Herein, an electrospray deposition (ESD) technique is investigated as an affordable method for obtaining micro/nanostructured surfaces. When processed via ESD from water:ethanol blends, methylcellulose (MC), a fibril gel former, can form nanowire coatings. These nanowires are formed via enhanced gelation by shear forces and surface charges that lead to electrospinning on a drop‐by‐drop basis. However, these ESD MC nanostructures can be easily destroyed upon water exposure. In this work, conformal coating of these MC nanostructures with atomic layer deposition (ALD) of Al2 O3 is explored to impart further stability. Upon subsequent heating of the ALD‐coated MC nanostructures, superhydrophobicity can be obtained. It is found that the final ALD‐coated structures exhibit a trade‐off between mechanical stability and hydrophobicity depending on MC nanowire size, with smaller wires being more mechanically robust and larger wires being more hydrophobic. Abstract : This study investigates the use of the electrospray deposition of methylcellulose, as it creates complex micro/nanostructured films, to be used in creating superhydrophobic surfaces through atomic layer deposition (ALD). Through changing spray conditions and heating following ALD, superhydrophobicity and surface durability are achieved and optimized in samples through a trade‐off between structural integrity and hydrophobicity.